2019
DOI: 10.21203/rs.2.17089/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A mixed-methods evaluation of a cluster randomized controlled trial on simulation-based low-dose, high-frequency plus mobile mentoring training versus traditional group-based training of health workers in Ebonyi and Kogi States, Nigeria

Abstract: Background: There are few studies from low- and middle-income countries on learning outcomes among health workers who have been trained on day of birth care using onsite, simulation-based, low-dose, high frequency (LDHF) training plus mobile (m) mentoring. The aim of this study was to compare their knowledge and skills competencies with those of health workers trained using the traditional offsite, group-based training (TRAD) approach in Kogi and Ebonyi states, Nigeria, over a 12-month period. Methods: We co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…This promotes maximum retention of clinical knowledge, skills, and attitudes (LGH 2020 ). A randomised controlled trial in Nigeria found that, when compared to traditional off-site lecture-style training, simulation-based LDHF training and mentoring in basic emergency obstetric and newborn care was more effective at improving health workers’ skills acquisition and retention (Ugwa et al 2020 ). However, the cost of simulators can be prohibitive for midwifery education institutions.…”
Section: Innovations For Midwives and Midwiferymentioning
confidence: 99%
“…This promotes maximum retention of clinical knowledge, skills, and attitudes (LGH 2020 ). A randomised controlled trial in Nigeria found that, when compared to traditional off-site lecture-style training, simulation-based LDHF training and mentoring in basic emergency obstetric and newborn care was more effective at improving health workers’ skills acquisition and retention (Ugwa et al 2020 ). However, the cost of simulators can be prohibitive for midwifery education institutions.…”
Section: Innovations For Midwives and Midwiferymentioning
confidence: 99%